Concomitant cardiac surgery and fixation of bilateral rib fractures sustained during cardiopulmonary resuscitation. Issue 12 (26th October 2022) - Comanici, Maria; Farmidi, Abu; Bhudia, Sunil K.; Anikin, Vladimir
Abstract: Background: Chest compressions during cardiopulmonary resuscitation (CPR) may cause sternal or rib fractures and chest wall instability. This can complicate medical management and significantly impair respiratory function. Surgical management of flail chest is technically demanding, and it becomes even more challenging if the patient requires a concomitant cardiac procedure. Case Presentation: A 78‐year‐old male suffered a cardiac arrest and sustained sternal and bilateral rib fractures during a successful CPR. He underwent a concomitant coronary artery bypass grafting and aortic valve replacement combined with stabilization of the chest wall. We discuss the possibility of fixation of bilateral rib fractures and its role in postoperative recovery after cardiac surgery. Conclusions: Chest wall stabilization for an already fragile patient, with impaired respiratory system performance, could help improve overall outcomes, pulmonary function, weaning from mechanical ventilation, and rehabilitation. It may be used together with a cardiac procedure for a life‐threatening cardiac pathology.